2016
DOI: 10.1177/0218492316650774
|View full text |Cite
|
Sign up to set email alerts
|

New technique for fixing rib fracture with bioabsorbable plate

Abstract: Fixation of a bone fracture with a bioabsorbable plate made of poly-L-lactide and hydroxyapatite has received attention. We adopted this technique for a rib fracture by bending the plate into a U-shape and fixing it with suture through the holes in the mesh of the plate and holes that are drilled in the edge of the fractured rib. The suture is also wound around the plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…[4][5][6][7] There have been several reports regarding the same u-HA/PLLA material in the field of chest surgery. [8][9][10] Those mentioned their different techniques from our techniques. Ito et al 8) performed fixation for rib-costal cartilage after thoracotomy using the mesh-type u-HA/ PLLA device, and Oyamatsu et al 10) also used meshtype device for rib fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] There have been several reports regarding the same u-HA/PLLA material in the field of chest surgery. [8][9][10] Those mentioned their different techniques from our techniques. Ito et al 8) performed fixation for rib-costal cartilage after thoracotomy using the mesh-type u-HA/ PLLA device, and Oyamatsu et al 10) also used meshtype device for rib fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Those mentioned their different techniques from our techniques. Ito et al 8) performed fixation for rib-costal cartilage after thoracotomy using the mesh-type u-HA/ PLLA device, and Oyamatsu et al 10) also used meshtype device for rib fractures. Tsunekawa et al 9) reported the use of intramedullary u-HA/PLLA pin after median sternotomy induce an earlier sternal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…A bioresorbalble plate consinsting of poly-l-lactic and unsintered and uncalcined hydroxyapatite, as SFMX, has superior osteoconductive properties, bonds bone fracture, and promotes good bone healing without pseudoarticulation [9]. Though there were many reports for fixing rib fracture with bioresorbable plate [9][10][11], the study for fixing median sternotomy with bioresorbable plate in cardiac surgery was few.…”
Section: Discussionmentioning
confidence: 99%
“…This mesh plate is resorbed in body in about 6 years while including osteoconduction [8]. SFMX has already been used for fixing rib fracture [9,10] or repair of flail chest [11]. Even more, Tanaka et al [12] reported that postoperative respiratory and hemodynamic condition were more stable with SFMX in fixing median sternotomy after congenital cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a variety of techniques have been used for the surgical fixation of rib fractures with varying recovery effects (Leinicke et al, 2013). The development of absorbable bone plates has received great attention for the treatment of rib fractures and maintenance of normal respiratory functions in the affected patients (Hur et al, 2016;Oyamatsu et al, 2016). The main rib fixation methods include anterior plate, intramedullary fixation, U-shaped plate and absorbable bone plate (Pieracci et al, 2017;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%